PERSEPSI GURU TERHADAP KEBIJAKAN DIGITALISASI PENDIDIKAN DAN DAMPAKNYA PADA KUALITAS PEMBELAJARAN DI SEKOLAH DASAR - Hikmah Puspasari; Subiantoro (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2026)
This study aims to identify teachers' perceptions of the education digitalization policy and analyze its impact on the quality of learning at the elementary school level. A qualitative approach was used, with data collected through in-depth interviews and field observations. The results indicate that most teachers view the digitalization policy as a positive step that helps improve efficiency and innovation in the learning process. Teachers acknowledge that digitalization facilitates access to information, enriches learning media, and enhances interaction with students. However, challenges remain, including unequal access to technology between urban and rural areas and a lack of ongoing mentoring, which hinder optimal implementation. Teachers' positive perceptions contribute to improved student learning outcomes, although progress in learning outcomes is still gradual. These findings recommend the need for strengthened ongoing training support and effective feedback mechanisms to enhance the success of digitalization in elementary schools.